Pemetaan Sasaran Marketing Calon Mahasiswa Baru UBHARA Jaya Menggunakan Algoritma C4.5 - Efrianto Nugroho Putro; Rafika Sari (Journal of Students‘ Research in Computer Science, 2023)
Information technology developed by higher education institutions must be able to solve problems and be the right solution for the effectiveness of the performance of a higher education institution. One of them is in predicting the acceptance of prospective new students which is an important process to test how much public interest is in becoming a student on a campus. In this study, a predictive model was built using a data mining approach. The purpose of this study is to show predictions of the acceptance of prospective new students regarding the attractiveness of prospective students at Bhayangkara Jakarta Raya University (Ubhara) when viewed from the location data of the prospective student's school of origin. So that Ubhara can adjust his marketing strategy in introducing the Ubhara to prospective students. This study uses a dataset of prospective new students who registered at Ubhara in 2019 and 2020 and selected 50 datasets as samples and applied data mining techniques using the C.45 algorithm. Data mining techniques are built through Python programming using the stages of data selection, checking for missing data values ​​and data transformation. The results of this study are used as an evaluation and recommendation for marketing using a confusion matrix, an accuracy rate of 60% is obtained. This can be improved by using more datasets. Keywords: C4.5 algorithm, new students, marketing strategy   Abstrak Teknologi informasi yang dikembangkan oleh lembaga pendidikan perguruan tinggi harus dapat menyelesaikan permasalahan dan menjadi solusi yang tepat bagi efektifitas kinerja sebuah perguruan tinggi. Salah satunya dalam melakukan prediksi penerimaan calon mahasiswa baru yang merupakan suatu proses penting untuk menguji seberapa besar daya tarik masyarakat untuk menjadi mahasiswa disuatu kampus. Pada penelitian ini, dibangunlah model prediksi melalui teknik pendekatan data mining. Tujuan penelitian ini yaitu menunjukkan prediksi penerimaan calon mahasiswa baru mengenai daya tarik calon mahasiswa Universitas Bhayangkara Jakarta Raya (Ubhara) jika dilihat dari data lokasi sekolah asal calon mahasiswa tersebut. Sehingga Ubhara dapat menyesuaikan strategi marketingnya dalam memperkenalkan Ubahar kepada calon mahasiswa.  Penelitian ini menggunakan dataset calon mahasiswa baru yang mendaftar ke Ubhara pada tahun 2019 dan 2020 dan dipilih 50 dataset sebagai sampel serta penerapan teknik data mining menggunakan algoritma C4.5. Teknik data mining dibangun melalui pemrograman Python dengan menggunakan tahapan-tahapan data seleksi, cek data missing values dan transformasi data. Hasil penelitian ini digunakan sebagai evaluasi dan rekomendasi untuk pemasaran menggunakan confusion matrix, diperoleh tingkat akurasi sebesar 60% hal ini dapat ditingkatkan dengan penggunaan dataset yang lebih banyak. Kata kunci: Algoritma C4.5, mahasiswa baru, sasaran marketing